Computational Fluid Dynamics Model on Updraft Gasifier Using Carbonized Woody Briquette as Fuel. (December 2017) - Lu, Ding; Yoshikawa, Kunio; Ismail, Tamer M.; El-Salam, M. Abd
Abstract: A two-dimensional unsteady mathematical model was developed to simulate the gasification/combustion process in the updraft fixed bed gasifier. The governing equations of two phases in the bed are discussed, and the sub-model of the process rate model and gas species production is determined. The particle size changes during the devolatilization and char burnout are also considered. To verify the model and to increase the understanding of the gasification characteristics, a set of experimental and numerical comparisons has been performed. The simulation results in the bed are accordant with the experimental results in prediction of the syngas composition and the carbon conversion. The results showed that the model proposed in this study is a promising tool for simulating the gasification/combustion process of biomass within a fixed bed gasifier.